A Comprehensive Evaluation of Road Safety Awareness Among Drivers and Motorists in Zamboanga Peninsula - Malang, Bernandino P.; Adel, Marjorie Jelly A.; Borja, Angelica T.; Mangray, Johair J. (Future Science / FSH-PH Publications, 2023)
Road safety is a matter of paramount concern on a global scale, given the substantial loss of life and injury resulting from road accidents every year. This comprehensive study is dedicated to a meticulous examination of road safety awareness and responsible conduct among drivers and motorists in Zamboanga Peninsula, situated in the Philippines. The central aim of this research is to conduct a detailed evaluation of the current status of road safety awareness and the responsible behaviors of drivers and motorists within Zamboanga Peninsula. Our intention is to identify the pivotal factors that influence road safety awareness and to recognize the barriers obstructing the translation of this awareness into responsible road behavior. To accomplish this aim, the researchers have employed quantitative techniques. A meticulously structured questionnaire survey was administered to a diverse cohort of drivers and motorists, which facilitated the collection of multifaceted data encompassing demographics, the level of awareness regarding road safety regulations, and the determinants impacting their on-road conduct. The quantitative dataset underwent rigorous analysis employing an array of statistical methods, with the mean scores and ranking system employed to dissect the collected data. The outcomes of this comprehensive research endeavor unveil a myriad of critical insights. Foremost, a conspicuous gender disparity is evident among road users in Zamboanga Peninsula, with males constituting the majority. Intriguingly, a substantial proportion of drivers falls within the age bracket of 26-35, signifying the demographic significance of this cohort. On the aspect of road safety awareness, the study affirms the presence of a robust understanding of fundamental road safety principles, yet it highlights the imperative need for focused attention to areas such as overtaking rules and the usage of mobile phones during driving. The research points to inconsistent law enforcement and high levels of traffic congestion as the most influential factors contributing to deficiencies in road safety awareness. This comprehensive study serves to illuminate the complex road safety landscape in Zamboanga Peninsula. It underscores the compelling necessity for region-specific interventions that cater to the prevalent gender and age disparities among road users. Moreover, the research findings emphasize the pivotal roles of law enforcement, traffic management, education, and targeted awareness campaigns in the quest for an improved road safety scenario.